Mean nutrient adequacy ratio and associated factors of complementary foods among children aged 6–23 months in Northeast Ethiopia - Kassaw, Abdulkerim; Chane Mekonnen, Tefera; Tadesse Amsalu, Erkihun; ABeje, Eyob Tilahun; Daba, Chala; Tsega, Yawkal; Endawkie, Abel (Frontiers in Pediatrics, 2025)
BackgroundInadequate intake of macro- and micronutrients is a significant public health challenge in Ethiopia. Ethiopia carries a substantial burden of both macro- and micronutrient deficiencies, with far-reaching consequences. However, there is limited evidence on the determinants and mean nutrient adequacy of complementary foods among children aged 6–23 months. Therefore, this study aims to determine the mean nutrient adequacy ratio and associated factors of complementary feeding among children aged 6–23 months in Northeast Ethiopia.MethodsA study was conducted in Northeast Ethiopia between 1 March and 30 April 2023, among 255 children aged 6–23 months. The study employed a systematic sampling technique to select 255 children. The data were collected using a 24-h dietary recall method. Linear regression analysis was conducted to identify factors associated with the nutrient adequacy of complementary foods. In the multivariable analysis, variables with p-values <0.05 were considered statistically significant.ResultsThe study found that the mean nutrient adequacy ratio of complementary foods among children aged 6–23 months in Northeast Ethiopia was 63% (95% CI 60.8–65.14). The adequacy of nutrients in complementary foods varied: energy (90%), fat (93%), carbohydrate (70%), protein (88%), calcium (57%), zinc (52%), vitamin B1 (50%), vitamin A (52%), and vitamin C (60%). The age of the child, mother's education, wealth index, feeding frequency, dietary diversity, minimum acceptable diet, source of information during antenatal care, postnatal care, food insecurity, and the number of children aged under 5 were associated with mean nutrient adequacy of complementary feeding.ConclusionsThe study concludes that the mean nutrient adequacy ratio of complementary foods among children aged 6–23 months in Northeast Ethiopia is alarmingly low, indicating a significant gap in meeting the nutritional recommendations set by the World Health Organization. Various factors, including the child's age, maternal education, household wealth index, food insecurity, and dietary diversity, were identified as critical determinants of nutrient adequacy. These findings underscore the urgent need for comprehensive interventions at multiple levels, including education, food security, and health services, to enhance the consumption of adequate and diverse complementary foods. By addressing these factors, stakeholders can improve the nutritional status of young children, ultimately contributing to better health outcomes and development in the region.